ANALISIS PENGUCAPAN DAN PEMBENTUKAN KATA KEANUAGL DALAM INSTA STORY SELEBGRAM - Afifah Wulandari; Lailis Saadah; Ummi Fatmawati (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2020)
The speech of language by someone is idiosyncratic or distinctive. Using a qualitative descriptive method, this study analyzed Keanuagl's pronunciation of the Insta Story Selebgram (ISS). Research data, in the form of words spoken by Keanuagl, were collected using the observation, note and record method. Data were analyzed by prescriptive analytic, meaning that they were compared with what should have been spoken. The results of the research data analysis are presented informally. This study found that phonological deviations were often carried out in the pronunciation or pronunciation performed by Keanuagl in the ISS. Some of the phoneme pronouncements done by Keanuagl do not match the proper pronunciation of the phonemes. In his speech, Keanuagl often performs phoneme removal, phoneme addition, and phoneme exchange.